2012
DOI: 10.1186/1472-6947-12-44
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of a picture archiving and communication system (PACS) in a Saudi Arabian hospital radiology department

Abstract: BackgroundCompared with the increasingly widespread use of picture archiving and communication systems (PACSs), knowledge concerning users’ acceptance of such systems is limited. Knowledge of acceptance is needed given the large (and growing) financial investment associated with the implementation of PACSs, and because the level of user acceptance influences the degree to which the benefits of the systems for healthcare can be realized.MethodsA Technology Acceptance Model (TAM) was used to assess the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 32 publications
6
56
2
3
Order By: Relevance
“…For example, research has shown that perceived usefulness and perceived ease of use may play a significant role in CDSS use among clinicians, but the influence of perceived ease of use is not significantly supported for other types of healthcare technologies [32]. Prior studies have found that TAM constructs are valid for healthcare professionals [2,25,26,38,39], but the perceived ease of use is not consistently related to attitudes [28,40]. …”
Section: Methodsmentioning
confidence: 99%
“…For example, research has shown that perceived usefulness and perceived ease of use may play a significant role in CDSS use among clinicians, but the influence of perceived ease of use is not significantly supported for other types of healthcare technologies [32]. Prior studies have found that TAM constructs are valid for healthcare professionals [2,25,26,38,39], but the perceived ease of use is not consistently related to attitudes [28,40]. …”
Section: Methodsmentioning
confidence: 99%
“…Malah, penerimaan dan kepuasan adalah penting dalam memasti kejayaan sesebuah pelaksanaan teknologi yang baharu di samping meningkat perkhidmatan terhadap penjagaan pesakit. Aldosari (2012) mendapati penerimaan pengguna perlu diambil kira apabila sesebuah organisasi ingin melaksana suatu sistem yang baharu seperti PACS.…”
Section: Abstrakunclassified
“…Kajian mengguna nilai Likert 1 hingga 5 dengan tiga konstruk faktor pengukuran bagi 20 item. Konstruk terdiri daripada persepsi kebergunaan (7 item), persepsi kemudahan penggunaan (4 item) dan kelakuan (9 item) yang membawa kepada penerimaan sistem PACS tersebut (Aldosari, 2012). Kajian mendapat kelulusan daripada Jawatan Kuasa Etika Penyelidikan Universiti Kebangsaan Malaysia (NN-058-2013).…”
Section: Kaedah Kajianunclassified
“…In another study conducted in Denmark (Bossen et al, 2013), healthcare staff found that vendor responsiveness and support was a significant factor during and after the deployment of a comprehensive EHR system in the hospital. Furthermore, Aldosari (2012) in his study about the acceptance of PACS within a healthcare institution in Saudi Arabia suggested that vendor support could influence the acceptance of such technologies since there are multiple suppliers for those HIS systems with each supplier having its own policy; the researcher also suggested to include this factor in future studies. The previous lines have demonstrated the importance of vendor support as a contributor to the adoption of HIS systems; as a result, the hypothesis for this construct is: H7: Vendor support will significantly influence the usage of HIS.…”
Section: Environmental Dimensionmentioning
confidence: 99%